Implicit Learning in Transient Global Amnesia and the Role of Stress - Nees, Frauke; Griebe, Martin; Ebert, Anne; Ruttorf, Michaela; Gerber, Benjamin; Wolf, Oliver T.; Schad, Lothar R.; Gass, Achim; Szabo, Kristina (Frontiers in Behavioral Neuroscience, 2016)
Transient global amnesia (TGA) is a disorder with reversible anterograde disturbance of explicit memory, frequently preceded by an emotionally or physically stressful event. By using magnetic resonance imaging (MRI) following an episode of TGA, small hippocampal lesions have been observed. Hence it has been postulated that the disorder is caused by the stress-related transient inhibition of memory formation in the hippocampus. In experimental studies, stress has been shown to affect both explicit and implicit learning – the latter defined as learning and memory processes that lack conscious awareness of the information acquired. To test the hypothesis that impairment of implicit learning in TGA is present and related to stress, we determined the effect of experimental exposure to stress on hippocampal activation patterns during an implicit learning paradigm in patients who suffered a recent TGA and healthy matched control subjects. We used a hippocampus-dependent aversive learning procedure (context conditioning with the phases habituation, acquisition, and extinction) during functional MRI following experimental stress exposure (socially evaluated cold pressor test). After a control procedure, controls showed successful learning during the acquisition phase, indicated by increased valence, arousal and contingency ratings to the paired (CON+) versus the non-paired (CON-) conditioned stimulus, and successful extinction of the conditioned responses. Following stress, acquisition was still successful, however extinction was impaired with persistently increased contingency ratings. In contrast, TGA patients showed impairment of conditioned responses and insufficient extinction after the control procedure, indicated by a lack of significant differences between CON+ and CON- for valence and arousal ratings after the acquisition phase and by significantly increased contingency ratings after the extinction. After stress, aversive learning was not successful with non-significant ratings of all parameters. Concerning brain activation patterns after the control procedure, controls showed increased hippocampal response during acquisition after the control procedure. This was not seen after stress exposure. In TGA patients, we observed an increased response in the right ventral striatum in the acquisition phase following stress. These findings suggest that alterations in implicit learning processes, including impaired hippocampal and increased striatal responses, might play a role in TGA pathophysiology, partly related to acute stress.